2015
DOI: 10.15288/jsad.76.1.143
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Injectable Naltrexone in U.S. Substance Use Disorder Treatment Programs

Abstract: ABSTRACT. Objective: Medication-assisted treatment for substance use disorders (SUDs) is not widely used in treatment programs. The aims of the current study were to document the prevalence of adoption and implementation of extended-release injectable naltrexone, the newest U.S. Food and Drug Administration-approved medication for alcohol use disorder (AUD), in U.S. treatment programs and to examine associations between organizational and patient characteristics and adoption. Method: The study used interview d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Finally, centers with greater reliance on insured clients were more likely to offer diverse treatments, making them more competitive in their operational environment. Other research has also found an association between reliance on competitive revenue and EBP adoption (Aletraris et al, 2015; Knudsen et al, 2006, 2007). …”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Finally, centers with greater reliance on insured clients were more likely to offer diverse treatments, making them more competitive in their operational environment. Other research has also found an association between reliance on competitive revenue and EBP adoption (Aletraris et al, 2015; Knudsen et al, 2006, 2007). …”
Section: Discussionmentioning
confidence: 87%
“…Similarly, structural resources, like access to prescribing staff and infrastructural supports for coordinated care found in larger, older, and hospital-based programs, have been demonstrated to facilitate innovation (Abraham et al, 2010; Knudsen et al, 2007; Roman and Johnson, 2002). Finally, center reliance on competitive funding may increase pressure to provide a wide-range of treatments as is the case with entrepreneurial centers dependent on private funds, clients with insurance, or with for-profit status (Aletraris et al, 2015; Knudsen et al, 2006; 2007). …”
Section: Introductionmentioning
confidence: 99%
“…However, initiation of naltrexone requires full detoxification from opioids (typically seven to ten days of abstinence from opioids), including from methadone and buprenorphine. Combined with the relatively higher costs of naltrexone, the requirement to be opioid-free prior to induction may limit its feasibility for many individuals (Aletraris et al, 2015;Lee et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of such studies have focused on oral buprenorphine, nding salient barriers to include a lack of training for physicians in MOUD and addiction treatment, concerns about diversion, insurance barriers, and discomfort in treating patients with comorbid psychiatric conditions (15,(24)(25)(26)(27)(28). Fewer studies have examined extended-release naltrexone; current research suggests that insurance-related factors, the requirement that patients are completely opioid-abstinent for 7 to 10 days prior to initiation, inadequate sta ng, and limited education for prescribing physicians are key barriers to prescribing extendedrelease naltrexone (10,(29)(30)(31)(32). Even though methadone for OUD cannot be prescribed outside of OTPs, o ce-based physicians can refer patients to these facilities for methadone treatment; but little is known about frequency of and barriers to this referral process.…”
Section: Access To Treatment For Opioid Use Disordermentioning
confidence: 99%